Caucasus: winning the shooting war, losing the media battle - Ong, Wei Chong (2016)
The rapidity and magnitude of Russia’s military response suggest that the Russian military is once more able to prosecute high-intensity joint-operations albeit of a limited kind. While Russian feat of arms might have won the day on the battlefield, in the arena of international opinion, it was a case of strategic defeat.